A Escrita do Eu. A Literatura como Laboratório da Vida - Gonçalo Marcelo (Classica Digitalia: Ideia, 2019)
This book, which comprises four different parts, divided into eighteen chapters, puts forward an analysis drawing both from philosophy and from literary hermeneutics. Its guiding thread are the creative or «poietic» processes through which the «self» forms and transforms itself as a configuration of symbols and a work of language, in the laboratory of (auto)biographic memory and imagination. The book sheds light on the open, exploratory and experimental character of literature in general and of the experiences of writing and narrating in particular. But it also emphasizes the elusive, unstable and perhaps never fully graspable trait of these experiences in a first person perspective. In the book, the processes of subjectivity and identity (personal or collective) are explored and the mechanisms for interpreting life and world are investigated.